PARTISIPASI PARTAI POLITIK LOKAL DALAM PERPOLITIKAN NASIONAL PADA KEANGGOTAAN DPD - Apri Rotin Djusfi; Phoenna Ath Thariq; Eza Aulia (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2020)
The existence of the Senate (DPD) can be summed up as a meeting between democratization and regional autonomy. The formation of the Senate (DPD) is of course to support regional interests in national policies to protect the Republic of Indonesia. Based on the formulation of problems described earlier regarding the participation of local political parties in national politics at DPD membership, the objectives of the study include examining the participation of local political parties to participate in national politics in DPD membership. Based on the research object above, this research is normative legal research (legal research). The position and function of the DPD are to bridge the local government to the central government in bringing the interests of the people in the regions. The existence of cadres of local political parties in the Senate (DPD) provides channels for the regions in the national decision-making process related to regional interests. Keyword: Senate, DPD, Political Parties